1983
DOI: 10.1007/bf00439212
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in Krabbe's disease: Comparison with neuropathology

Abstract: We report computed tomography (CT) appearance of two patients with Krabbe's disease. The most common findings included severe brain atrophy: an enlarged frontal extracerebral space, dilatation of ventricles, enlarged cisterns and enlarged cortical sulci. There was low attenuation in the corpus medullaris of the cerebellum, and symmetrical focal hypodensity in the central periventricular white matter. CT at the terminal stage (16 months) showed marked cerebral atrophy including flattening of the heads of caudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…According to Garcia et al 5 and to Harcourt et al 10 ONE in KD could represent an initial phase, an early neuroimaging correlate of this condition, prior to subsequent atrophy. 11 Ieshima et al 7 and Jones et al , 3 in previously reported cases of ONE in KD state that this enlargement is due to the accumulation of numerous globoid cells suggesting that neuronal tissue outside the brain may react differently, with enlargement rather than atrophy in response to the presence of cerebroside in Krabbe disease. 3,7 Several disorders should be included in the differential diagnosis of KD: optic nerve glioma with dural ectasia, frequently in type 1 neurofbromatosis; nerve sheath meningioma; granulomatous or histiocytic infltration of optic nerves, leukemia, orbit pseudotumor, juvenile xanthogranuloma, post viral optic neuritis; optic nerve medulloepithelioma; and retinoblastoma with optic nerve compromise.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Garcia et al 5 and to Harcourt et al 10 ONE in KD could represent an initial phase, an early neuroimaging correlate of this condition, prior to subsequent atrophy. 11 Ieshima et al 7 and Jones et al , 3 in previously reported cases of ONE in KD state that this enlargement is due to the accumulation of numerous globoid cells suggesting that neuronal tissue outside the brain may react differently, with enlargement rather than atrophy in response to the presence of cerebroside in Krabbe disease. 3,7 Several disorders should be included in the differential diagnosis of KD: optic nerve glioma with dural ectasia, frequently in type 1 neurofbromatosis; nerve sheath meningioma; granulomatous or histiocytic infltration of optic nerves, leukemia, orbit pseudotumor, juvenile xanthogranuloma, post viral optic neuritis; optic nerve medulloepithelioma; and retinoblastoma with optic nerve compromise.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 Typically, on CT images, early in the disease, high density is seen bilaterally in the thalami, caudate nuclei, corona radiate, and cerebellar dentate nuclei. As the disease progresses, diffuse white matter atrophy ensues.…”
Section: Discussionmentioning
confidence: 99%
“…CT findings of infantile GLD in previous reports are summarized as folIows: In an early stage, symmetrical increased attenuation is recognized in the thalami, caudate nuclei, braim stern, cerebellum and corona radiata with or without patchy low density in the deep white matter of the cerebral and cerebellar hemispheres and minor cerebral atrophy (1-5, 10, 13, 14). Later, diffuse atrophy accompanied with ventriculomegaly and low density changes in the central white matter was recognized (1,2,4,7,10).…”
Section: Discussionmentioning
confidence: 98%
“…There may be relatively less low density on the white matter of GLD compared with that of other leukodystrophies (7). MR showed decreased Tl values with normal or slightly decreased T2 values in deep gray matter of hemispheres, brain stern and periventricular or capsular white matter even in the early stages.…”
Section: K Tadaetalmentioning
confidence: 97%
“…In his original article, Krabbe described 1 out of 5 children to have solid, hard, and thickened optic nerves. 8 Optic nerve enlargement 3,9,10 in early infantile Krabbe's disease may be an isolated finding or may be seen in association with cervical cord enlargement 10 or enlargement of other cranial nerves. 11 Bernal and Lenn 12 reported the first case of early infantile Krabbe's disease with enhancement of bilateral III, V, VIII, X, and XI cranial nerves without en- More importantly in our patient, the enhancing cranial nerves were not enlarged; however, no enhancement was seen along the enlarged prechiasmatic optic nerves.…”
Section: Discussionmentioning
confidence: 99%